Cross-reaction with Borrelia burgdorferi antigen of sera from patients with human immunodeficiency virus infection, syphilis, and leptospirosis. - Raoult, D (1989)
We have studied the cross-reaction with Borrelia burgdorferi of sera positive for leptospirosis, syphilis, or human immunodeficiency virus by using the microimmunofluorescence test (micro-IF). The percentage of sera reactive in the micro-IF before absorption varied from 7 to 37% and was reduced to 3 to 8% after absorption with a commercial Reiter treponemal antigen. The cross-reaction of sera positive for syphilis or human immunodeficiency virus was distinguished from the homologous reaction with sera from patients with Lyme disease in the immunoblot test results. However, the cross-reaction could not always be distinguished from the homologous reaction with sera from patients with leptospirosis whose sera scored positive in the micro-IF for B. burgdorferi.